Implementasi Model Pembelajaran Quantum Learning dalam Meningkatkan Motivasi Belajar - Achmad Maulidi (Fakta: Jurnal Pendidikan Agama Islam, 2022)
Learning with the Quantum Learning model seeks to maximize all elements contained in learning including all the potential and abilities that exist in students. This is intended to make the learning carried out by the teacher maximum and the students also maximally absorb the material presented. The main focus of this study is to determine the application of the Quantum Learning learning model in increasing student learning motivation, the effectiveness of applying the model and the factors that support and hinder the application of the Quantum Learning learning model.  Based on the results of the study,  the role of teachers in the application of the Quantum Learning learning model  makes teachers closer to students so as to provide a comfortable atmosphere when starting teaching and learning activities in the classroom. The application of this  model has a positive effect on increasing student motivation, as seen from the  enthusiasm of students participating in teaching and learning activities in the classroom, the students are very interested in honing their skills. The supporting factors in the application of  the Quantum Learning  learning model are the teacher's example, the activeness and discipline of the teacher and parents as the main control holders in building student learning motivation, while the obstacles are the lack of media, and time constraints.